The Development of a Work Stress Model for Air Traffic Controllers in Indonesia - Saleh, Lalu Muhammad; Russeng, Syamsiar Siang; Tadjuddin, Istiana; Yanti, Iva Hardi; Syafitri, Nurul Mawaddah; Yusbud, Mahfuddin; Rahmadani, Yulianah (UI Scholars Hub, 2022)
The workload complexity experienced by and expected air traffic controllers (ATCs) causes psychological fatigue, engenders stressful conditions, and affects their quality of life. This study investigated the development of a model of psychological fatigue in ATCs in Indonesia, which affected their work stress levels and quality of life. This cross-sectional, three-month study focused on 185 ATCs randomly selected from six AirNavs based on strata. The results indicated a relationship between work duration (p-value = 0.033) and stress on ATCs; additionally, a relationship between work time and the opportunity to meet personal life needs (p-value = 0.007) were found. Feelings of tiredness among ATCs manifested as a ‘thirsty throat’ feeling, and in saturation measurements, no respondents had experienced hypoxia in the two months of observation. Structural equation modeling showed that psychological fatigue had no direct effect on the quality of life; however, it had an indirect and significant effect on work stress (p-value = 0.001). It can be concluded that the stress conditions experienced by the ATCs have a palpable effect on feelings of fatigue and quality of life.